The cause and effect of wise investment decisions in Malaysia: a qualitative approach / Arifha Mohamad, Nor Suziwana Tahir and Yarina Ahmad - Mohamad, Arifha; Tahir, Nor Suziwana; Ahmad, Yarina (Universiti Teknologi MARA, 2020)
In the global stock market environment, individual shareholders have become a central issue for irrational thinking towards investment decision making. They are recognized as one of the investor groups that is highly exposed to investment risks and losses. The key aspects of the issues are mainly attributed to their limited knowledge, skills, and expertise. This paper seeks to remedy these problems by examining the challenges in making wise investment decisions among individual shareholders in Malaysian Public Listed Companies and recommendations from key stakeholders' perspectives. The methodological approach taken in this study is a qualitative design based on interviewing the key stakeholders (board members, and representatives of Bursa Malaysia and Minority Shareholder Watchdog Group). With the help of the NVivo software in managing the data, this study analyses the data and concludes that there are four challenges and four recommendations in making wise investment decisions among individual shareholders. The findings can be categorized into internal challenges (investment culture and investment knowledge) and external challenges (dissemination of information and voting power). The recommendations are also grouped into internal recommendations (diversification and research) and external recommendations (company representative and annual report). This paper does not engage with the overview from the individuals themselves and requires further research. This study offers some important insights for investors, companies and policymakers.